Improving Health Status in The Elderly Through Health Checks and Education at Nuriah Nursing Homes in Karimun. - Dini Mulyasari; Rachmawaty M. Noer; Novika Sari; Ermawaty Ermawaty; Faizal Triharyadi; Dewi Tampubolon; Sarkissian Catherine (Yayasan Adra Karima Hubbi, 2023)
Background. Elderly is the final stage of development in human life. Everyone who goes through old age will experience various changes. Purpose. From the results of data collection for the elderly at the Nuriah Nursing Home, Kec.Sei Lakam, Kab. Karimun can identify the main problem in the elderly, namely the risk of declining health status of the elderly as evidenced by the existence of health problems such as CKD, high blood pressure, heart disease, rheumatism, paralysis and diabetes mellitus. Method. The method used is by conducting health checks and counseling followed by 5 elderly people. Results. The results of this activity showed that from 5 elderly people, 1 elderly had hypertension because the elderly underwent dialysis 2 times a week. 1 elderly suffers from malnutrition. 1 elderly had dementia, and one elderly experienced long bed rest. Conclusion. The conclusion is that 70% are all carried out / assisted by orphanage officers. Starting from bathing, clothes, chapters and tubs. The elderly seem to understand how to improve health status.